Cooperative movement in Japan - Hoynden, Yoshio (Maruzen Co., 1958)
This book the cooperative movement in Japan has not been closely associated with the labor movement, as it often is in other countries. ... It was not until Dr. Toyohiko Kagawa and his asso- ciates organized consumers cooperatives at Osaka and Kobe in 1920 that the Rochdale principles were fully observed.